Comparative Analysis of Cost Effectiveness of Ceftriaxone and Cefotaxime Antibiotic Therapy in Inpatients with Typhoid Fever in Aulia Pandeglang Regional Hospital in 2023 - Yusransyah, Yusransyah; Rustiyani, Risa; Nurani, Agnes Wieanita; Stiani, Sofi Nurmay; Udin, Baha; Halimatusyadiah, Leni (Journal of Experimental and Clinical Pharmacy (JECP), 2025)
Typhoid fever is still a significant health problem for children in developing countries, including Indonesia. This disease is caused by infection with Salmonella Typhi bacteria, which is a Gram-negative bacteria and requires treatment with antibiotics. The use of antibiotics usually takes up a large portion of the hospital treatment budget. This study aims to compare the cost-effectiveness between two types of antibiotics, namely ceftriaxone and cefotaxime, in typhoid fever patients at Aulia Pandeglang Hospital, and to find the most cost-efficient treatment. This study is descriptive and observational, with retrospective data collection. The data used came from medical records and cost records of inpatients with typhoid fever in children aged 1 to 11 years at Aulia Pandeglang Hospital in 2023. A total of 20 patients met the study criteria. The outcomes measured in this study were the average length of stay in the hospital. The cost components calculated consisted of direct medical costs, such as drug costs, action costs, inpatient costs, medical device costs, and laboratory fees. The analysis was conducted from the payer's perspective. The results showed that the cost for the effectiveness of using ceftriaxone and cefotaxime was IDR 15,264 and IDR 18,265, with an ICER of IDR 257.9 to increase the effectiveness of cefotaxime. The conclusion of this study is that ceftriaxone is a more cost-effective antibiotic.